Chilling injuri as related to climacteric behaviour in plums - Candan, Ana Paula; Graell, Jordi; Larrigaudière, Christian (Springer, 2025)
7th International Symposium on the Plant Hormone Ethylene held in Pisa (Italy), June 18-22, 2006